Bariatric surgery on the morbidity and mortality of SARS-CoV-2 infection - Castillo-de la Cruz, Ayumi (2021)
Background:The COVID-19 pandemic has had a big impact around the world and as obesity is an important risk factor for the severe form of the SARS-CoV-2 disease, bariatric surgery will have a great clinical impact. Performing this surgery in people with obesity implies weight loss, which has multiple beneficial effects such as reducing the inflammatoryresponse,increasingimmunityandimproving cardiopulmonary and kidney function. This review is intended to provide updated information on bariatric surgery in the morbidity and mortality of SARS-CoV-2 infection. Expecting that it provides support tothereaderinordertounderstandthepathophysiological mechanisms involved in the better prognosis and lower probability of hospitalization and mortality from COVID-19, pending comparison of obese patients who have not undergone bariatric surgery